Intrinsically piezoelectric elastomer based on crosslinked polyacrylonitrile for soft electronics. (1st December 2022) - Fu, Rumin; Tu, Lingjie; Guan, Youjun; Wang, Zhengao; Deng, Chunlin; Yu, Peng; Tan, Guoxin; Ning, Chengyun; Zhou, Lei
Abstract: Soft and elastic piezoelectric materials have critical applications in emerging fields such as wearable electronics and soft robotics. Although there is much progress towards piezoelectric elastomers, existing methods to achieve such materials rely mainly on blending piezoelectric ceramic or polymer fillers into elastomers. Here, we report a soft tissue-like polyacrylonitrile (PAN)-based piezoelectric elastomer, which shows a high piezoelectric coefficient d33 of ∼ 40 pC/N and an intrinsic super-elasticity (100 % self-recovery). Moreover, ultrahigh compressibility (> 99 % strain) and stretchability (> 250 % strain) are achieved simultaneously for the elastomer. The elastomer can produce long-term stable electrical outputs and exhibit a fast piezoelectric response and high sensitivity due to the stress-induced poling effect. We proceed to demonstrate that the piezoelectric elastomers can be used for simultaneous impact protection and self-sensing, as well as continuous human pulse and complex hand movements monitoring. These results suggest that the material has potential applications for soft electronics. Graphical Abstract: ga1 Highlights: Elastomeric polymer with competitive piezoelectric properties was designed. The piezoelectric polymer has ultrahigh compressibility and stretchability. The piezoelectric polymer can produce long-term stable electrical outputs. The polymer exhibit a fast piezoelectric response and high sensitivity. The polymer could be used energy-absorbing smart material and health monitoring.